2003
DOI: 10.1021/jm0203985
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 7-Substituted Ginkgolide Derivatives:  Potent Platelet Activating Factor (PAF) Receptor Antagonists

Abstract: Ginkgolides are structurally unique constituents of Ginkgo biloba extracts and are known antagonists of the platelet-activating factor (PAF) receptor. Ginkgolide C is 25-fold less potent than ginkgolide B as a PAF receptor antagonist, due to the presence of the 7beta-OH. Recently, we found that 7alpha-fluoro ginkgolide B was equipotent to ginkgolide B underlining the critical importance of the 7-position of ginkgolides for PAF receptor activity. Herein we describe the synthesis of a series of ginkgolide B deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 27 publications
1
47
0
3
Order By: Relevance
“…In general, 10-OH is the most reactive for alkylation and esterification. [35] However, acid-catalyzed esterification, [36] reaction of GC (3) with alkyl and aryl sulfonyl halides in the presence of pyridine [37,38] as well as silylation [39] takes place at 7-OH; a selective silylation at 1-OH in the presence of imidazole has also been described. [40] The use of solid-phase synthesis (SPS) for the preparation of ginkgolide derivatives appeared to be particularly attractive, as the presence of multiple hydroxyl groups provides several options for connecting points.…”
Section: Resultsmentioning
confidence: 99%
“…In general, 10-OH is the most reactive for alkylation and esterification. [35] However, acid-catalyzed esterification, [36] reaction of GC (3) with alkyl and aryl sulfonyl halides in the presence of pyridine [37,38] as well as silylation [39] takes place at 7-OH; a selective silylation at 1-OH in the presence of imidazole has also been described. [40] The use of solid-phase synthesis (SPS) for the preparation of ginkgolide derivatives appeared to be particularly attractive, as the presence of multiple hydroxyl groups provides several options for connecting points.…”
Section: Resultsmentioning
confidence: 99%
“…Biological effects of ginkgolides can markedly vary with minor differences in their chemical structure. For example, the presence of one extra hydroxyl group at position 7 converts GB, a potent PAFR antagonist (K i ϭ 0.88 M) into GC, a constituent with much lower activity (K i ϭ 12.6 M) (Vogensen et al, 2003). Indeed, GA and GJ are the components of the extract that inhibit or even eliminate the deadly effects of A␤ on LTP (Nakanishi, 2005).…”
Section: Egb 761 and Ginkgolide A Inhibit A␤ Oligomerizationmentioning
confidence: 99%
“…As a result, they participate in the development of SAP and aggravate the injuries of pancreas and other organs or even cause SIRS, ARDS and MOF [4] . BN52021, one of the effective components of Chinese medicine ginkgo biloba leaf and a strong antagonist against the inflammatory medium of PAF, can not only block the signal transduction of PAF but also decrease blood concentration of PAF to exert its biological effect [17] . This study showed that BN52021 could decrease serum amylase level and alleviate pathological changes in SAP, which is consistent with that reported by other researchers [18,19] .…”
Section: Discussionmentioning
confidence: 99%